2005
DOI: 10.1179/136485905x19838
|View full text |Cite
|
Sign up to set email alerts
|

Significant decrease in the prevalence ofWuchereria bancroftiinfection in anopheline mosquitoes following the addition of albendazole to annual, ivermectin-based, mass treatments in Nigeria

Abstract: A prospective entomological survey was conducted in four sentinel villages in central Nigeria from 1999-2002, to assess the impact of annual, single-dose, mass drug administrations (MDA), with a combination of ivermectin and albendazole, on the transmission of Wuchereria bancrofti. As they were also endemic for human onchocerciasis, the four villages had received annual MDA based on ivermectin alone for 7 years prior to the addition of albendazole. Resting Anophelines gambiae s. l., An. funestus and Culex spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…An integrated MDA program was launched in 1997 with the objective of ‘piggy-backing’ schistosomiasis control (with praziquantel MDA) and LF elimination (with ivermectin/albendazole combination MDA) onto the river blindness ‘platform.’ [26] Prior to adding albendazole to the onchocerciasis MDA program, entomological and epidemiological studies were conducted in 1998–1999. These studies confirmed that the seven years of ivermectin monotherapy for onchocerciasis had not halted LF transmission in the onchocerciasis endemic LGAs [27], [28].…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…An integrated MDA program was launched in 1997 with the objective of ‘piggy-backing’ schistosomiasis control (with praziquantel MDA) and LF elimination (with ivermectin/albendazole combination MDA) onto the river blindness ‘platform.’ [26] Prior to adding albendazole to the onchocerciasis MDA program, entomological and epidemiological studies were conducted in 1998–1999. These studies confirmed that the seven years of ivermectin monotherapy for onchocerciasis had not halted LF transmission in the onchocerciasis endemic LGAs [27], [28].…”
Section: Methodssupporting
confidence: 54%
“…Collections in odd numbered compounds were also added when numbers of mosquitoes were few during the dry season. Indoor resting mosquitoes were collected in the morning using the pyrethrum knockdown (PK) technique as previously described [28]. The dead and dying mosquitoes that fell onto sheets draped throughout the compound living area were collected by forceps and placed in Petri dishes having moist tissue.…”
Section: Methodsmentioning
confidence: 99%
“…LF mapping in 1998 designated all 30 LGA for combined ivermectin and albendazole mass treatment for LF. Prior to launching the larger LF treatment programme, we sought (in 1999) entomology sentinel sites for a longitudinal study of treatment impact on LF transmission [9]. To identify villages with high baseline infection rates, our team captured and dissected resting Anopheles gambiae sl and An.…”
Section: Resultsmentioning
confidence: 99%
“…Indoor-resting mosquitoes were collected as described. 23,24 The dead and dying mosquitoes that were collected were immediately placed in Petri dishes containing moist tissue, and the dishes were kept in coolers with wet towels until dissections were performed, always on the day of collection and usually in the same village. Each mosquito was identified as An.…”
Section: Methodsmentioning
confidence: 99%